Skin status for predicting pressure ulcer development: A systematic review and meta-analyses. (November 2018) - Shi, Chunhu; Dumville, Jo C.; Cullum, Nicky
Abstract: Background: People with altered skin status are conventionally considered to have a higher risk of developing new ulcers. However, the evidence underpinning this potentially prognostic relationship is unclear. Objectives: To systematically review the evidence for the prognostic association of skin status with pressure ulcer risk. Methods: We performed a comprehensive electronic database search in February 2017 to identify longitudinal studies that considered skin status in multivariable analysis for predicting pressure ulcer risk in any population. Study selection was conducted by two reviewers independently. We collected data on the characteristics of studies, participants, skin status, and results of multivariable analyses of skin status–pressure ulcer incidence associations. We applied theQ ualityI nP rognosisS tudies tool to assess risk of bias. We conducted meta-analyses using STATA where data were available from multivariable analyses. We used the Grades of Recommendation Assessment, Development and Evaluation approach to assess the certainty of evidence generated from each meta-analysis. Results: We included 41 studies (with 162, 299 participants, and 7382 having new ulcers) that investigated 15 skin descriptors. Participants were predominantly hospitalised adults and long-term care residents (with a median age of 75.2 years). Studies had a median follow-up duration of 7.5 weeks. 61.0% (25/41) of studies were judged as being high risk of bias. 53.7% (22/41) of studies had small sample sizes. Subsequently, the certainty of evidence was rated as low or very low for all 13 meta-analyses that we conducted though all analyses showed statistically significant associations of specific skin descriptors–pressure ulcer incidence. People with non-blanchable erythema may have higher odds of developing pressure ulcers than those without (Odds Ratio 3.08, 95% Confidence Interval 2.26–4.20 if pressure ulcer preventive measures were not adjusted in multivariable analysis; 1.99, 1.76–2.25 if adjusted) (both low-certainty evidence ). The evidence for other skin descriptors was judged as very low-certainty and their prognostic value is uncertain. Conclusions: There is low-certainty evidence that people with non-blanchable erythema may be more likely to develop new pressure ulcers than those without non-blanchable erythema. The evidence for the prognostic effects of other skin descriptors (e.g., history of pressure ulcer) is of very low-certainty. The findings support regular skin assessment and preventive action being taken in the presence of non-blanchable erythema. Given the millions at risk of ulceration and the widely recommended use of skin status as part of risk assessment there is a need for more, high quality confirmatory studies.